UPAYA MENINGKATKAN KESADARAN MELALUI SOSIALISASI MATERIAL RUMAH TAHAN GEMPA DI SMKN 26 JAKARTA - Sumeru, Indrawati; Sutjipto, Suradjin; Pontan, Darmawan; Lahji, Khotijah (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
This community service program at SMK 26 Jakarta has the main aim of increasing students' understanding and readiness in facing the threat of earthquakes. With a focus on education about earthquake-resistant house materials, this program not only provides technical knowledge about safe construction, but also seeks to change student behavior in building an environment that is more resilient to earthquakes. Through collaboration between schools, local governments, disaster management institutions and the community, this program is expected to be able to create a real impact in increasing awareness of disaster risks and preparedness to face them. By encouraging active participation from all relevant parties, including students, this program emphasizes the importance of collaboration in preparing the people of Jakarta to face potential earthquake disasters. Thus, this service is not just about conveying information, but also about building a community that is aware of risks and prepared to act